A STUDY ON PROCEDURE OF COMMUNITY HEALTH CARE CHANDI SUB-DISTRICT, CHAWANG DISTRICT, NAKHON SI THAMMARAT PROVINCE - Chotirat, Prasit; Nunklam, Direk; ., Phrakru Viratdhammachot; Chimhad, Pairat (Journal of MCU Nakhondhat, 2024)
This research aimed to 1) Study the health promotion process in the Chan Di subdistrict community and 2) Study recommendations for improving the health promotion process in the Chan Di subdistrict community, Chawang District, Nakhon Si Thammarat Province. The research employed a mixed-method approach, including qualitative research through unstructured interviews with key informants, such as the director of the subdistrict health-promoting hospital, village health volunteers, and representatives of the local population, selected by purposive sampling, with a total of 21 participants. The quantitative aspect involved a sample of 180 residents of the Chan Di subdistrict community, selected using Krejcie and Morgan’s table. A questionnaire was used as the research tool, which was validated by experts and checked for reliability. The results showed that the questionnaire was reliable and applicable. The research findings were as follows: 1) The overall health promotion process in the Chan Di subdistrict community, Chawang District, Nakhon Si Thammarat Province, across all five aspects, had a high average score ( = 3.58, S.D. = 0.93). 2) The recommendations for the health promotion process in the Chan Di community revealed that the process considered the health of the health-promoting hospital staff and village health volunteers, who needed to be capable of promoting their own health, lead a health-promoting lifestyle, and serve as role models for the public. Health promotion activities were adjusted to fit with the services provided by the health-promoting hospital, and additional health promotion activities were suggested, including health consultation services. The components of the Chan Di community health promotion process included 1) Promotion, prevention, treatment, rehabilitation, and protection, 2) Patient screening, 3) Systematic diagnosis and referral, 4) Health education, 5) Proactive operations, 6) Networking with partners, and 7) Understanding the community context.